2022
DOI: 10.1084/jem.20220615
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated neurostimulation promotes circuit rewiring and unlocks recovery after spinal cord injury

Abstract: Functional recovery after incomplete spinal cord injury depends on the effective rewiring of neuronal circuits. Here, we show that selective chemogenetic activation of either corticospinal projection neurons or intraspinal relay neurons alone led to anatomically restricted plasticity and little functional recovery. In contrast, coordinated stimulation of both supraspinal centers and spinal relay stations resulted in marked and circuit-specific enhancement of neuronal rewiring, shortened EMG latencies, and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Therefore, other strategies such as neuronal stimulation may need to be combined for motor recovery. Previous studies show that axon sprouting is promoted by neuronal stimulation, and the stimulation leads to recovery of motor function 1316 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other strategies such as neuronal stimulation may need to be combined for motor recovery. Previous studies show that axon sprouting is promoted by neuronal stimulation, and the stimulation leads to recovery of motor function 1316 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, chemogenetic stimulation of spinal neurons using designer receptors activated only by designer drugs (DREADDs), can induce axon sprouting and restore locomotion after SCI by administering actuator ligands 15 . In addition, such chemogenetic stimulation of CSNs in both supraspinal centers and spinal relay stations results in enhancement of neuronal rewiring and locomotor recovery 16 .…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the better outcome in functional recovery at high doses could be explained because AAV-retro/Cre injections below the injury may be promoting rewiring and synaptic plasticity of intraspinal circuitry, whereas injections above the injury may be deleting PTEN in supra spinal centers that promote CST growth after injury. Recent studies have shown that coordinated growth stimulation in supra spinal centers and in spinal relay stations led to enhancement in neuronal rewiring and improved locomotor recovery (Van Steenbergen et al, 2023). The combination of these effects may elicit a stronger recovery of function than what is observed with intermediate doses of AAV-retro/Cre.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic conductivity of a natural spinal cord ranges between 10 −2 and 10 −1 S cm −1 [24]. When SCI occurs, the electronic signal pathway between the afferent and efferent neurons is disrupted, leading to the loss of motor and sensory function [20].…”
Section: The Significance Of Electronic Signals In Sci Repairmentioning
confidence: 99%
“…Spinal cord contains numerous neural connections that can transfer stimuli from afferent neurons to efferent neurons in the form of electrical signals, directing appropriate responses in muscles and glands [19]. When injury occurs, the signaling pathway between afferent and efferent neurons is disrupted, preventing the normal transmission of electrical signals to the other side, and resulting in loss of motor function and abnormal sensory functions [20]. Benefiting from the progress of biomaterial scaffolds in nerve injury repair and nerve function regeneration, rational design of nerve regeneration scaffolds with electrical activity can not only mimic the electronic conductivity of the natural spinal cord, but also facilitate the delivery of drugs, cytokines, or cells to target sites [12,21].…”
Section: Introductionmentioning
confidence: 99%